The Effect of 12-Week Calisthenics Exercise on Physical Fitness among Obese Female Students - Mohd Hassan Sakinah; Nor Fazila Abd Malek; Azizuddin Khan Thariq Khan; Asmadi Ishak; Hairul Anuar Hashim; Keong Chen Chee (OVS LLC, 2022)
Study purpose. The main purpose of this study was to determine the effect of calisthenics exercise on physical fitness. Materials and methods. 28 obese female students aged 20-30 with a BMI ranging between 30 kg/m2 and 35 kg/m2 were involved in this study. Participants were randomly divided into three groups which comprised a calisthenics exercise group, an aerobic calisthenics exercise and a control group. Sit and reach test (flexibility), sit up test (muscular endurance) and 20-meter shuttle run test (cardiovascular endurance) were measured as physical fitness parameters. All the tests were conducted before and after a 12-week intervention training program. Results. The results of this study indicate that the calisthenics and aerobic calisthenics groups had significant (p < 0.05) improvement in the sit and reach test performance compared to the control group. The aerobic calisthenics group also showed significant (p < 0.05) improvement in the sit up and 20-metre shuttle run test performance compared to the calisthenics and control groups. Conclusions. In conclusion, these study findings demonstrated that calisthenics exercise when combined with aerobic exercise was more effective to improve flexibility, muscular endurance and cardiovascular endurance among obese female students compared to calisthenics exercise only. Therefore, it is suggested that fitness trainers should consider combining calisthenics exercise with aerobics in the training program to improve flexibility, muscular and cardiovascular endurance.